Patriarchal Representation of Husband Wife Domestic Roles on Social Media: A Maqasid al-Shariʿah Analysis of TikTok Content Narratives - Nabila, Zahro; Ahsan, Khoirul (Al-Fikru: Jurnal Ilmiah, 2026)
TikTok has become a major platform for producing and disseminating gender narratives in Indonesia, including those concerning the domestic roles of husbands and wives. This study examines the representation of patriarchy in TikTok content through the perspective of Maqāṣid al-Sharī’ah. Using a qualitative approach with qualitative content analysis, ten TikTok videos were purposively selected from four relevant hashtags in April 2026. Data were analyzed using semiotic analysis and normative evaluation based on Maqāṣid al-Sharī’ah. The findings identify three narrative typologies: Type A (critique of patriarchy, 60%), Type B (reproduction and legitimization of patriarchy, 30%), and Type C (contrastive narratives, 10%). Despite its lower frequency, Type B generated higher average viewership, suggesting greater algorithmic visibility and cultural acceptance. From the Maqāṣid perspective, patriarchal narratives potentially undermine ḥifẓ al-nafs, ḥifẓ al-nasl, and ḥifẓ al-’aql by diminishing women’s dignity, weakening family relationships, and reinforcing ideological echo chambers. The study concludes that Maqāṣid al-Sharī’ah offers a constructive framework for fostering reciprocal, just, and compassionate marital relationships based on mu’āsharah bi al-ma’rūf.